Inhibitory mechanism of 5-bromo-3-indoleacetic acid for non-structural-3 helicase hepatitis C virus with dynamics correlation network analysis. (December 2018) - Rahman, Mueed Ur; Rehman, Ashfaq Ur; Liu, Hao; Chen, Hai-Feng
Graphical abstract: Community networks for free and bound states indicate the different inhibitor mode. Highlights: Hepatitis C virus, Nonstructural 3 helicase (NS3h) protein is a well-studied segment of Non-structural 3/4 A helicase-protease protein that is crucial for the RNA duplex unwinding and RNA translocation during the process of HCV replication. Helicase is a potential target for antiviral drugs. Compound 2t9 (5-bromo-1 H -indol-3-yl acetic acid) has been identified through the integrated strategies and considered as a potential lead compound for the inactivation of HCV helicase. In the current study, using all-atom molecular dynamic simulation and correlations network strategy, we scrutinized the inhibitory mechanism of compound 2t9 that needs to be elucidated for the improvement of indole-based and similar HCV helicase inhibitors. Consequently, by comparing the structural dynamics of free (NS3h WT ) and bound (NS3h/2t9 WT ) protein, we identified that the inhibitor-bound protein achieved a conformation resemblance to the open conformation, where the RNA is displaced results in destabilization of RNA-binding cleft, disruption in ATP/ADP binding site and alter the inter-domain communication. The information based on detailed dynamic aspects of the drug targeted protein will facilitate the researchers in the development of HCV antiviral drugs. Abstract: Hepatitis C virus, Nonstructural 3 helicase (NS3h) protein is a well-studied segment of Non-structural 3/4 A helicase-protease protein that is crucial for the RNA duplex unwinding and RNA translocation during the process of HCV replication. Similar to other HCV nonstructural proteins, helicase is a potential target for antiviral drugs and several antiviral molecules have been used to target the RNA-binding cleft, despite the fact that none of those helicase antivirals have advanced the clinical trials. Compound 2t9 (5-bromo-1 H -indol-3-yl acetic acid) has been identified through the integrated strategies and considered as a potential lead compound for the inactivation of HCV helicase. This inhibitor bind to the 3´-terminal RNA-binding cleft, and reduced the RNA binding and unwinding activity of the targeted protein. In the current study, using all-atom molecular dynamic simulation and correlations network strategy, we scrutinized the inhibitory mechanism of compound 2t9 that needs to be elucidated for the improvement of indole-based and similar HCV helicase inhibitors. Consequently, by comparing the structural dynamics of free (NS3h WT ) and bound (NS3h/2t9 WT ) protein, we identified that the inhibitor-bound protein achieved a conformation resemblance to the open conformation, where the RNA is displaced results in destabilization of RNA-binding cleft, disruption in ATP/ADP binding site and alter the inter-domain communication. The results were evaluated by using the W501 L mutated system. The information based on detailed dynamic aspects of the drug targeted protein will facilitate the researchers in the development of HCV antiviral drugs.